Long-Term Effects of a Very Low Carbohydrate Compared With a High Carbohydrate Diet on Renal Function in Individuals With Type 2 Diabetes: A Randomized Trial. Issue 47 (November 2015) - Tay, Jeannie; Thompson, Campbell H.; Luscombe-Marsh, Natalie D.; Noakes, Manny; Buckley, Jonathan D.; Wittert, Gary A.; Brinkworth, Grant D.
Abstract : Abstract: To compare the long-term effects of a very low carbohydrate, high-protein, low saturated fat (LC) diet with a traditional high unrefined carbohydrate, low-fat (HC) diet on markers of renal function in obese adults with type 2 diabetes (T2DM), but without overt kidney disease. One hundred fifteen adults (BMI 34.6 ± 4.3 kg/m 2, age 58 ± 7 years, HbA1c 7.3 ± 1.1%, 56 ± 12 mmol/mol, serum creatinine (SCr) 69 ± 15 μmol/L, glomerular filtration rate estimated by the Chronic Kidney Disease Epidemiology Collaboration formula (eGFR 94 ± 12 mL/min/1.73 m 2 )) were randomized to consume either an LC (14% energy as carbohydrate [CHO < 50 g/day], 28% protein [PRO], 58% fat [<10% saturated fat]) or an HC (53% CHO, 17% PRO, 30% fat [<10% saturated fat]) energy-matched, weight-loss diet combined with supervised exercise training (60 min, 3 day/wk) for 12 months. Body weight, blood pressure, and renal function assessed by eGFR, estimated creatinine clearance (Cockcroft–Gault, Salazar–Corcoran) and albumin excretion rate (AER), were measured pre- and post-intervention. Both groups achieved similar completion rates (LC 71%, HC 65%) and reductions in weight (mean [95% CI]; −9.3 [−10.6, −8.0] kg) and blood pressure (−6 [−9, −4]/−6[−8, −5] mmHg), P  ≥ 0.18. Protein intake calculated from 24 hours urinary urea was higher in the LC than HC group (LC 120.1 ± 38.2 g/day, 1.3 g/kg/day; HC 95.8 ± 27.8 g/day, 1 g/kg/day), P  < 0.001 diet effect. Changes in SCr (LC 3 [1, 5], HC 1 [−1, 3] μmol/L) and eGFR (LC −4 [−6, −2], HC −2 [−3, 0] mL/min/1.73 m 2 ) did not differ between diets ( P  = 0.25). AER decreased independent of diet composition (LC −−2.4 [−6, 1.2], HC −1.8 [−5.4, 1.8] mg/24 h, P  = 0.24); 6 participants (LC 3, HC 3) had moderately elevated AER at baseline (30–300 mg/24 h), which normalized in 4 participants (LC 2, HC 2) after 52 weeks. Compared with a traditional HC weight loss diet, consumption of an LC high protein diet does not adversely affect clinical markers of renal function in obese adults with T2DM and no preexisting kidney disease.